PENANGANAN PELANGGARAN TINDAK PIDANA POLITIK UANG OLEH PANITIA PENGAWAS KABUPATEN KUNINGAN PADA PILKADA KUNINGAN DITINJAU DARI UU NO. 10 TAHUN 2016 - Ikhsan Bayanulloh; Sarip Sarip (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2020)
The characteristics of a democratic state can be applied that in the hands of the people the ownership of the highest sovereignty is located, this is also in line with the contents of the constitution as stated in the provisions of Article 1 paragraph (2) of the 1945 Constitution. The concrete form of the implementation of democracy can be seen from the implementation of elections both to elect members of the legislature and or executive as well as regional head elections which are held directly by prioritizing the priority of the indicators, namely implementation in the implementation process, applicable legal rules, and how to enforce election law. As a system and mechanism, elections are expected to be carried out freely and equally/freely and fairly. Theories and ideas regarding the definition of the rule of law are numerous to be our reference in understanding it. According to Immanuel Kant in his book Methaphisiche Ansfangsgruunde der Rechtslehre, he expressed his opinion on the concept of a liberal rule of law state. The role and authority of the Kuningan Panwaskab in handling election crime violations is quite good although it still has limitations in carrying out its authority, in addition to problems in handling criminal offenses in Law no. 10 of 2016, the Panwaskab often found indecision as well as law enforcers, the prosecutor's office and the police who were members of the Gakkumdu center. Keywords: Crime, Money Politics, Pilkada, Supervisor.